Eksperimen Pembelajaran Matematika Dengan Strategi Ekspositori Dan Stad Terhadap Hasil Belajar Siswa Ditinjau Dari Motivasi Belajar Siswa Kelas VII Semester Gasal SMP Negeri 1 Gatak Tahun Pelajaran 2016/2017 - Ervina, Darti; , Drs. Slamet HW, M.Pd (2017)
The purpose of research this are: (1) Effect of mathematics learning with strategy expository and STAD toward student learning outcomes, (2) The effect of the level of student motivation toward student learning outcomes, (3) Effects of the use of learning strategies and student motivation toward student learning outcomes , The research quantitative type is quasi-experimental. The population in this study are all odd semester students of class VII SMP Negeri 1 Gatak the academic year 2016/2017. Samples taken in this study were 64 students, consisting of 32 students as an experimental class and 32 students as the control class. The sampling technique used was cluster random sampling. Data collection techniques through tests, questionnaires, and documentation. Data were analyzed using two-way analysis of variance with a cell is not the same. The results of the data analysis with a significance level α = 5%, namely: (1) There is a learning strategy influence on the results of students mathematics learning. (2) There is no effect on learning outcomes motivation to learn mathematics. (3) There is no interaction learning strategies and students motivation to learn math student outcomes.